The Function of Reduplication in Conveying Multifaceted Meanings within Madurese Vocabulary: A Sociolinguistic and Cross-Linguistic Analysis of Its Interaction with Other Linguistic Components - Jaftiyatur Rohaniyah; Rini Listyowati; Ina Daril Hanna; Linta Wafdan Hidayah; Beny Hamdani (Tell : Teaching of English Language and Literature Journal, 2025)
: The phenomenon of reduplication in the Madurese language is essential for enriching vocabulary and facilitating nuanced communication. This research explores the sociolinguistic and cross-linguistic aspects of reduplication in Madurese, emphasizing its diverse meanings and its interplay with other linguistic components. Our analysis seeks to reveal the ways in which reduplication influences cultural and social interactions among speakers of Madurese. Employing a qualitative methodology, data was collected through observations and interviews with native speakers. A comparative sociolinguistic approach was utilized to examine reduplication in Madurese in relation to analogous patterns in Javanese and Indonesian, underscoring the impact of contextual, cultural, and linguistic factors on meaning. The results demonstrate that reduplication in Madurese fulfills various functions, including the expression of plurality, intensity, and emotional nuances. Reduplicated nouns typically denote plurality, whereas adjectives indicate intensification, showcasing functions that differ from those in Javanese and Indonesian. This research enhances our comprehension of the multifaceted role of reduplication in Madurese, illustrating its contribution to linguistic identity and cultural representation. These results highlight the significance of studying reduplication to grasp the processes of meaning-making within sociolinguistic frameworks.